A new look at HRM practice and its Relationships to employees' attitudes: A comparison of public and private Sector in Malaysia. - Kee , Daisy Mui Hung

(untitled)
The research project explores employees understanding of HRM practice in the workplace. HRM practice has gained amplified interest in the management field due to its impact on employees' work related attitudes and behaviors. Even though organizations provide employees with its HRM practice, the expectation is to keep employees motivated and productive. How HRM practice impacts on the different forms of employees work related attitudes and behaviors in different sector is not clear. Past researchers showed evidence linkages between HRM, employees' level of commitment and their turnover intention. We propose that HRM practice influences employees work related outcomes in both public and private sector in different ways. Seven component of HRM practice namely job design,HR planning, recruitment and selection, training and development, compensation and performance management and employee relations have been chosen a focal point to investigate the above relationship. Data was collected through self administered questionnaire distributed to both public and private sector. The results indicate HRM practices have a significant influence on employees work outcome.HRM in both public and private sector differ significantly.Finally implication of the findings limitation and future direction are discussed.